2022
DOI: 10.12688/f1000research.76032.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of fear, anxiety, obsession and functional impairment of COVID-19 amongst health-care workers and trainees: A cross-sectional study in Nepal

Abstract: Background: The emergence of the COVID-19 epidemic threw the world into turmoil. The medical community bore the brunt of the pandemic's toll. Long work hours, and a lack of personal protective equipment (PPE) and social support all had an influence on mental health. Methods: This cross-sectional study was conducted among Lumbini Medical College Teaching Hospital students and employees in Palpa, Nepal. Data entailing their demographic details, pre-existing comorbidities, or death in the family due to COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
(25 reference statements)
1
1
0
Order By: Relevance
“…Result of hypothesis one is significantly possible considering that more of the older hospital workers compared to the younger ones had dysfunctional thinking with COVID-19 (COVID-19 obsession). Result of this study reflected the findings of Atreya, et al, (2022), significant association between COVID-19 fear and age were found. Also, Srivastava, et al (2020) reported that higher age group had significant COVID-19 obsession.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Result of hypothesis one is significantly possible considering that more of the older hospital workers compared to the younger ones had dysfunctional thinking with COVID-19 (COVID-19 obsession). Result of this study reflected the findings of Atreya, et al, (2022), significant association between COVID-19 fear and age were found. Also, Srivastava, et al (2020) reported that higher age group had significant COVID-19 obsession.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, findings of a web-based study among Indian population showed that the prevalence of obsession due to COVID-19 was 12.47%. Furthermore, significant higher obsession score was found among females compared to males (Srivastava, Bala, Srivastava, Mishra, Shamim, & Sinha, 2020).In relation to age, findings of a cross-sectional study among students and employees of Lumbini Medical College Teaching Hospital Palpa, Nepal, significant association between COVID-19 fear and age was reported (Atreya, Nepal, Menezes, Shurjeel, Qazi, Ram, Usman, Ghimire, Marhatta, Islam, Sapkota, & Garbuja, 2022). Cunning and Hodes, (2021) reported that COVID-19 pandemic appears to be associated with obsessivecompulsive symptoms in younger people.…”
Section: Introductionmentioning
confidence: 92%